A Compact Short-Channel Analytical Drain Current Model of Asymmetric Dual-Gate TMD FET in Subthreshold Region Including Fringing Field Effects - Niraj Kumar Singh; Monika Kumari; Manodipan Sahoo (IEEE Access, 2020)
A compact drain current model is developed for an asymmetric, dual gate, monolayer 2 - D Transition metal dichalcogenide (TMD) field effect transistor (FET) in the subthreshold region. The work includes the effect of source to drain tunneling and gate dielectric fringing effects. The model is systematically derived for an asymmetric, dual gate structure. The model developed is also extended into a dual-gate symmetric structure. The characteristic length expression has only physical and dimensional parameters including the contribution of fringing field effects from both front and back gate dielectric. The model is validated with simulation results obtained using NEGF based nanodevice simulators and experimental data of WSe2 p-channel FET. Also, transfer characteristics, output characteristics, subthreshold swing and output resistance are compared with reported data in literatures. A close agreement is observed with some disparity arising because of the non-inclusion of back gate fringing effects and source to drain tunneling in their models. The proposed model captures the effects of different high-κ gate dielectric materials and its thicknesses. Impact of temperature is also studied on transfer characteristics. The model is also scalable from ultrashort channel regime to long channel regime. Finally, the model can be applicable not only for TMD materials but other 2 - D materials also.